Peer and land-based approaches for fostering empowering and healthy relationships with Indigenous and northern young people in the Northwest Territories - Gittings, Lesley; Malama, Kalonde; Logie, Carmen; Lys, Candice; Taylor, Shira B.; McNamee, Clara; Mackay, Kayley Inuksuk; Admassu, Zerihun (PloS one, 2024)
Indigenous and Northern women in Canada experience high rates of intimate partner violence (IPV), and this is particularly true in the Northwest Territories (NWT). Adolescents are also at increased risk of IPV, which has far-reaching, lifelong effects. Indigenous youth are particularly vulnerable to IPV due to ongoing effects of intergenerational trauma caused by colonialism, racism and residential school legacies. We explored attitudes towards IPV and the healthy relationship knowledge, skills, and experiences among participants of Fostering Open eXpression among Youth (FOXY) and Strength, Masculinities, and Sexual Health (SMASH) Peer Leader Retreats in the NWT. Multi-method approaches included quantitative surveys youth completed before and immediately following retreats. Quantitative analysis from retreats (2018–2021) included 240 participants aged 12–19 (mean age 14.5) who reported ever having an intimate partner. Most were from the FOXY program (64.2%), Indigenous (69.6%) and heterosexual (66.4%). Qualitative methods included Focus Group Discussions (FGD) (n = 69) conducted with peer leaders and apprentices (n = 311) and youth and adult staff (n = 14 FGDs, n = 165 participants). We thematically analysed FGDs to explore healthy relationship knowledge and skills, alongside paired t-tests to examine pre/post retreat changes in attitudes towards IPV. Qualitative findings suggest that leadership and embodied learning were effective in equipping youth with violence prevention and healthy relationship skills. While young women were committed to sharing knowledge and skills about healthy relationships in their communities, young men resonated with values of respect and appreciated support to identify and express emotions. Participants across programmes demonstrated their belief that healthy intimate relationships have communal, relational and intergenerational benefits. Quantitatively, we found a statistically significant reduction in attitudes accepting of IPV among young women, but no changes were noted among young men. Findings contribute to emergent evidence on strengths-based, culturally-responsive IPV prevention programming. Components of effective IPV prevention programming with young men merit further exploration.